Biocomputing 2018 2017
DOI: 10.1142/9789813235533_0034
|View full text |Cite
|
Sign up to set email alerts
|

Codon bias among synonymous rare variants is associated with Alzheimer’s disease imaging biomarker

Abstract: *Corresponding AuthorAlzheimer's disease (AD) is a neurodegenerative disorder with few biomarkers even though it impacts a relatively large portion of the population and is predicted to affect significantly more individuals in the future. Neuroimaging has been used in concert with genetic information to improve our understanding in relation to how AD arises and how it can be potentially diagnosed. Additionally, evidence suggests synonymous variants can have a functional impact on gene regulatory mechanisms, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…For instance, traditional genetic analyses of complex diseases rarely evaluate the effects of synonymous codon usage biases because they are generally thought to not contribute significantly to disease. However, recent studies have shown that synonymous codon usage alone significantly alters protein levels and can have a causal effect on Alzheimer's disease ( 44 ), cancer ( 45 , 46 ) and multiple sclerosis ( 45 ). CUBAP enables researchers to query synonymous codon usage biases in genes identified in case-control studies to determine the extent to which codon usage biases already exist within various populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, traditional genetic analyses of complex diseases rarely evaluate the effects of synonymous codon usage biases because they are generally thought to not contribute significantly to disease. However, recent studies have shown that synonymous codon usage alone significantly alters protein levels and can have a causal effect on Alzheimer's disease ( 44 ), cancer ( 45 , 46 ) and multiple sclerosis ( 45 ). CUBAP enables researchers to query synonymous codon usage biases in genes identified in case-control studies to determine the extent to which codon usage biases already exist within various populations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a synonymous mutation in UBE1 associated with developing X-linked infantile spinal muscular atrophy significantly lowers UBE1 expression and changes exon methylation ( 43 ). Synonymous rare variants are also associated with Alzheimer's disease biomarkers ( 44 ), and shifts in codon usage biases alone can yield high diagnostic accuracy in a variety of other diseases including cancers and multiple sclerosis ( 45 ). Furthermore, codon usage biases in rat oncogenes directly regulate tumor growth ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
“…Four SNPs in the exon were synonymous codons. In another study on Alzheimer's disease, several genes related to the disease were associated with synonymous variants (Miller et al 2018). Therefore, these studies suggest that synonymous codons are worth studying for the detection and prevention of disease.…”
Section: The Cdna and Genomic Structure Of Rrm1mentioning
confidence: 92%
“…Nucleotide sequence changes in coding regions are primarily assessed using protein-level conservation analysis that assesses their effect on protein sequence (see below). However, nucleotide-level conservation analysis may be considered useful for investigating effect of sequence changes on the fitness of splicing regulatory motifs, or mRNA secondary structure and stability, translation efficiency [22][23][24], or to infer functional importance of non-coding sequences (introns, untranslated regions and other extragenic sequence). Indeed, it is a factor denoted for review of synonymous variants (code BP7) in the ACMG/AMP guidelines [5].…”
Section: Nucleotide-level Evolutionary Conservationmentioning
confidence: 99%